Biosynthesis of β-nicotinamide mononucleotide from glucose via a new pathway in Bacillus subtilis - Tan, Zhilei; Yang, Yihang; Wu, Yannan; Yan, Jiajia; Zhang, Bin; Hou, Ying; Jia, Shiru (Frontiers in Microbiology, 2024)
β-nicotinamide mononucleotide (β-NMN) is an essential precursor of nicotinamide adenine dinucleotide (NAD + ) and plays a key role in supplying NAD + and maintaining its levels. Existing methods for NMN production have some limitations, including low substrate availability, complex synthetic routes, and low synthetic efficiency, which result in low titers and high costs. Herein, we constructed high-titer, genetically engineered strains that produce NMN through a new pathway.Bacillus subtilis WB600 was used as a safe chassis strain. Multiple strains overexpressing NadE, PncB, and PnuC in various combinations were constructed, and NMN titers of different strains were compared via shake-flask culture. The results revealed that the strain B. subtilis PncB1-PnuC exhibited the highest total and extracellular NMN titers. Subsequently, the engineered strains were cultured in a 5-L fermenter using batch and fed-batch fermentation. B. subtilis PncB1-PnuC achieved an NMN titer of 3398 mg/L via fed-batch fermentation and glucose supplementation, which was 30.72% higher than that achieved via batch fermentation. This study provides a safe and economical approach for producing NMN on an industrial scale.